Tracing elementary students’ learning trajectories of surface area in museum-based activities - Octaria, Dina; Zulkardi; Putri, Ratu Ilma Indra; Hiltrimartin, Cecil (Jurnal Elemen, 2026)
Understanding the surface area of three-dimensional shapes remains challenging for elementary students, particularly in distinguishing between area and perimeter and in connecting two-dimensional representations to three-dimensional objects. This study aims to trace elementary students’ learning trajectories on the surface area of cubes and cuboids through museum-based activities to support spatial literacy development. The study employed a design research methodology with a validation study approach, consisting of preliminary design, a pilot experiment, a teaching experiment, and a retrospective analysis. Participants were 44 fifth-grade students from an elementary school in Palembang, Indonesia. Data were collected through classroom observations, students’ worksheets, video recordings, and interviews, and analyzed qualitatively by comparing the Hypothetical Learning Trajectory (HLT) with the Actual Learning Trajectory (ALT). The results show that the museum context supported students’ spatial visualization, reasoning, and communication by enabling them to identify geometric attributes of artefacts, construct and validate nets, and derive surface area formulas through guided reinvention. The targeted use of Augmented Reality (AR) further supported students during critical transitions between two-and three-dimensional representations. The synthesis of the HLT and ALT yielded a validated Learning Trajectory, which was abstracted into a Local Instructional Theory (LIT) for teaching surface area in elementary geometry.